2020
DOI: 10.1002/adma.201905823
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Oxide Nanomaterials: Synthesis, Properties, and Theranostic Applications

Abstract: Despite the comprehensive applications in bioimaging, biosensing, drug/gene delivery, and tumor therapy of manganese oxide nanomaterials (MONs including MnO2, MnO, Mn2O3, Mn3O4, and MnOx) and their derivatives, a review article focusing on MON‐based nanoplatforms has not been reported yet. Herein, the representative progresses of MONs on synthesis, heterogene, properties, surface modification, toxicity, imaging, biodetection, and therapy are mainly introduced. First, five kinds of primary synthetic methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
234
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 389 publications
(244 citation statements)
references
References 290 publications
1
234
0
Order By: Relevance
“…[4] Over the past two decades, manganese oxide nanomaterials (MONs) have drawn attention in biomedical applications. [5] For example, He et al developed honeycomb MnO 2based nanoplatforms for intracellular glutathione (GSH)triggered drug release and photodynamic/gene-silencing dual therapy. [6] Despite these discoveries, the intrinsic immunogenicity and potential immune response of MONs remain unclear.…”
mentioning
confidence: 99%
“…[4] Over the past two decades, manganese oxide nanomaterials (MONs) have drawn attention in biomedical applications. [5] For example, He et al developed honeycomb MnO 2based nanoplatforms for intracellular glutathione (GSH)triggered drug release and photodynamic/gene-silencing dual therapy. [6] Despite these discoveries, the intrinsic immunogenicity and potential immune response of MONs remain unclear.…”
mentioning
confidence: 99%
“…Manganese oxide, an excellent MRI contrast agent, has been widely used in MRI. 66 In 2008, An et al designed hollow manganese oxide (MnO) NPs of different sizes for use in MRI. 67 The authors found that the T 1 relaxation was enhanced with increasing surface area, and that the hollow structures had a drug-loading capacity.…”
Section: Photothermal-based Therapy For Cancer Treatmentmentioning
confidence: 99%
“…To date, several synthetic strategies have been proposed to prepare MnO x -based nanomaterials with different sizes and morphologies, including the thermal decomposition method [61], exfoliation strategy [62], adsorption-oxidation method [63,64], hydro-/solvothermal method [65], and permanganate reduction method [66,67]. These methods show their intrinsic advantages and disadvantages [68]. For example, the thermal decomposition strategy can precisely regulate the particle size and morphology but the oily solventcapping surface limits the biomedical applications of the products.…”
Section: Preparation and Characterization Of Em Nss And Emdmentioning
confidence: 99%